Peran Roh Kudus Berdasarkan Teks Yohanes 14:26 dalam Pendidikan Kristen Anak Usia Dini - Wiranto, Derry; Kristanto, Samuel Hans (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2024)
This study examines the implications of the Holy Spirit's role as Teacher and Reminder (John 14:26) for Early Childhood Christian Education (ECCE). Through literature review and theological analysis, it explores how this understanding transforms ECCE practices, curriculum development, and pedagogical approaches. The research reveals that integrating the Holy Spirit's work requires a holistic approach, including responsive curriculum design, experiential teaching methods, and spiritually nurturing environments. It emphasizes educators' roles as facilitators sensitive to the Holy Spirit's guidance and the need for collaboration between ECCE institutions, families, and churches. The study addresses challenges in implementing a Spirit-centered approach and offers practical solutions. It proposes a paradigm shift in ECCE from knowledge transfer to facilitating transformative spiritual experiences, thus laying a robust spiritual foundation for the next generation.